2018
DOI: 10.14202/vetworld.2018.1331-1337
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance of bovine viral diarrhea and rift valley fever infections in camel

Abstract: Aim:This study was designed to investigate the current epidemiological situation of bovine viral diarrhea virus (BVDV) and rift valley fever virus (RVFV) infection of camels originating from Sudan “smuggler” and Egypt as part of our future plan for a national surveillance program in Egyptian provinces, which will aid in establishment of control strategy for animal diseases.Materials and Methods:This investigation was accomplished using serological diagnostic and molecular biology techniques. A total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The virus was recently reported in many other wildlife animals, such as white-tailed deer, free-range deer, and captive angulates in a zoo [8,17,18]. Several BVDV infections were reported in dromedary camels from several African countries such as Sudan, Egypt, and Algeria [19][20][21]. This is in addition to other outbreaks reported in Asian countries such as the Kingdom of Saudi Arabia, India, and Iran [12,22,23].…”
Section: Discussionmentioning
confidence: 87%
“…The virus was recently reported in many other wildlife animals, such as white-tailed deer, free-range deer, and captive angulates in a zoo [8,17,18]. Several BVDV infections were reported in dromedary camels from several African countries such as Sudan, Egypt, and Algeria [19][20][21]. This is in addition to other outbreaks reported in Asian countries such as the Kingdom of Saudi Arabia, India, and Iran [12,22,23].…”
Section: Discussionmentioning
confidence: 87%
“…Of the 388 eligible articles, 183 were excluded for multiple reasons described in Figure 1. Finally, a total of 205 articles (629 data on prevalence and/or CFR) met the inclusion criteria for this systematic review (Abakar et al., 2014; Abdallah et al., 2016; Adamu, 2020; Adamu et al., 2021; Adesiyun et al., 2020; Ahmed et al., 2018, 2020; Alhaji, 2020; Andayi et al., 2014; Andriamandimby et al., 2010; Andriamandimby et al., 2018; Aradaib et al., 2013; Archer et al., 2011, 2013; Atuman et al., 2022; Ayari‐Fakhfakh et al., 2011; Ba et al., 2012; Baudin et al., 2016; Beechler et al., 2015; van den Bergh et al., 2022; Bett et al., 2019; Bird et al., 2008; Bisimwa et al., 2016; Bloland et al., 2010; Blomstrom et al., 2016; Bob et al., 2017, 2022; Bonney et al., 2013; Bosworth et al., 2016; Boushab et al., 2015, 2016; Boussini et al., 2013, 2014; Breiman et al., 2010; Budasha et al., 2018; Budodo et al., 2020; Bukbuk et al., 2014; Centers for Disease Control and Prevention 2007; Chambaro et al., 2022; Chengula et al., 2014; Chevalier et al., 2005, 2011; Cichon et al., 2021; Clements et al., 2019; Cook et al., 2017; Cosseddu et al., 2021; Di Nardo et al., 2014; Diallo et al., 2005; Dione et al., 2022; Dondona et al., 2016; Durand et al., 2003, 2020; Dutuze et al., 2020; Ebogo‐Belobo et al., 2022; Eckstein et al., 2022; El Bahgy et al., 2018; El Mamy et al., …”
Section: Resultsmentioning
confidence: 99%
“…Two studies on RVFV prevalence in camels before 2010 showed that RVFV was low in camels from Giza, even during the 1977 RVF epidemic [ 35 , 52 ]. However, in recent decades, camel seropositivity rates for RVFV antibodies in both the Nile Valley and Upper Egypt governorates were greater than 20% [ 9 , 53 ]. In addition, in a survey published in 2009, the seropositivity rate was 15.10% in pigs from Alexandria (northern Egypt) and 13.95% in humans who are in frequent contact with pigs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%